Co-administration of MDR1 and BCRP or EGFR/PI3K inhibitors overcomes lenvatinib resistance in hepatocellular carcinoma - Sun, Dawei; Liu, Juan; Wang, Yunfang; Dong, Jiahong (Frontiers in Oncology, 2022)
Lenvatinib is the first-line treatment for hepatocellular carcinoma (HCC), the most common type of primary liver cancer; however, some patients become refractory to lenvatinib. The underlying mechanism of lenvatinib resistance (LR) in patients with advanced HCC remains unclear. We focused on exploring the potential mechanism of LR and novel treatments of lenvatinib-resistant HCC. In particular, we established a Huh7 LR cell line and performed in vitro, bioinformatic, and biochemical assays. Additionally, we used a Huh7-LR cell-derived xenograft mouse model to confirm the results in vivo. Following LR induction, multidrug resistance protein 1 (MDR1) and breast cancer resistance protein (BCRP) transporters were markedly upregulated, and the epidermal growth factor receptor (EGFR), MEK/ERK, and PI3K/AKT pathways were activated. In vitro, the co-administration of elacridar, a dual MDR1 and BCRP inhibitor, with lenvatinib inhibited proliferation and induced apoptosis of LR cells. These effects might be due to inhibiting cancer stem-like cells (CSCs) properties, by decreasing colony formation and downregulating CD133, EpCAM, SOX-9, and c-Myc expression. Moreover, the co-administration of gefitinib, an EGFR inhibitor, with lenvatinib retarded proliferation and induced apoptosis of LR cells. These similar effects might be caused by the inhibition of EGFR-mediated MEK/ERK and PI3K/AKT pathway activation. In vivo, co-administration of lenvatinib with elacridar or gefitinib suppressed tumour growth and angiogenesis. Therefore, inhibiting MDR1 and BCRP transporters or targeting the EGFR/PI3K pathway might overcome LR in HCC. Notably, lenvatinib should be used to treat HCC after LR induction owing to its role in inhibiting tumour proliferation and angiogenesis. Our findings could help develop novel and effective treatment strategies for HCC.